A new approach on the torison and curvature tensors in supermanifolds - Ali, Md. Showkat (BRAC University, 2010)
In this paper geometric space, super space, supermanifold, superconnection, the torsion and the curvature tensors are studied and some new notions of local forms of the torsion and curvature tensors are established, for deriving certain constraints in classical case called the super Bianchi identities.